(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the Lead Fracture in Permanent Pacemakers: Evaluation from the Anatomical and Technical Perspective. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at the Department of Electrophysiology at Hayat Abad Medical Complex Peshawar from 2008 to 2018. Materials and Methods: We conducted this study in the Pace Maker suite of the Medical Complex Peshawar, Pakistan. We retrospectively examined our pacemaker’s implantation records for any complication during the procedure and soon after the device implantation during the hospital stay. Apart from this, all those patients who came for pacemakers follow up with and without symptoms, were critically examined for any mal function of devices based on clinical examination, twelve lead ECG and pacemakers programming. X-ray chest and fluoroscopy examination were advised based on initial assessment if needed. The data so obtained was analyzed for complication of pacemaker’s implantation. Results: Total 670 patients’ data were analyzed in the study period. Five cases (0.3%) of lead fracture were identified from the record. One was during the procedure due to excessive force on the knot over the sleeve. There was one patient with subclavian crush syndrome and the cause remains unidentified in other two patients. Two patients were symptomatic at presentation and two were caught incidentally in follow up clinic. Conclusion: Lead fracture is not an uncommon complication which can be best prevented, if the procedure is done in way keeping in view the possible causes of the complication.